Association between amount of sleep, daytime sleepiness and health‐related quality of life in schoolchildren. (22nd February 2016) - Gustafsson, Marja‐Liisa; Laaksonen, Camilla; Aromaa, Minna; Asanti, Riitta; Heinonen, Olli J.; Koski, Pasi; Koivusilta, Leena; Löyttyniemi, Eliisa; Suominen, Sakari; Salanterä, Sanna
Abstract: Aims: To analyse the association between amount of sleep and daytime sleepiness and health‐related quality of life in schoolchildren during adolescence and to study the effect of age on this association. Background: Sufficient sleep is essential for the health of children and adolescents. Sleep influences almost all dimensions of life. Design: A 5‐year prospective follow‐up study (2004–2010) following 568 Finnish schoolchildren aged between 10‐15. Methods: The amount of sleep and perceived daytime sleepiness were assessed by a special questionnaire added to The Health Behaviour in School‐aged Children questionnaire. The Finnish version of the Paediatric Quality of Life Inventory was used to assess health‐related quality of life. The data were collected in 2004, 2006 and 2009/2010. Data were analysed with hierarchical linear mixed models. Results/findings: The more daytime sleepiness occurred, the lower the health‐related quality of life was and similar linear association was seen in every age group. The amount of sleep was significantly positively linearly associated with health‐related quality of life but not persistent across age groups. Positive association was significant at 15 years of age but not at other age groups. Similar linear association between daytime sleepiness and school‐related sub scores was also found. Conclusion: Sufficient sleep is essential for health‐related quality of life and should be protected and measured in the school health service.